Potential Antiviral Effect of Chloroquine Therapy against SARS-CoV-2 Infection - Musa, Imad R. (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: The coronavirus disease 2019 (COVID-19) pandemic has affected many countries with increasing morbidity and mortality. In the absence of an effective vaccine and medication, chloroquine may be a potential choice. AIM: This study aims to explore the role of the possible antiviral effects of chloroquine against SARS-CoV-2. MATERIALS AND METHODS: A systematic search of studies relating to the antiviral effects against coronaviruses was conducted between January 1, 1990, and up to May 26, 2020, for relevant studies using PubMed, Scopus, and Google Scholar. RESULTS: A total of 174 articles were initially identified. Ninety-seven papers were removed for failing to address the aim of the study. Seventy-seven full-text articles were retrieved for eligibility analysis. Ten studies focused on general inhibition of viral replication, ten evaluated its effects on angiotensin-converting enzyme 2, 19 addressed the effects on alkalizing the cellular pH, 25 concentrated on the immunomodulatory effect, two assessed the potential effects on sialic acid, and 24 explored the therapeutic outcome. CONCLUSION: Chloroquine has promising antiviral effects on SARS-CoV-2 at different levels.